The Role of Family Support in Foot Care Compliance among Patients with Type 2 Diabetes Mellitus: Family Influence on Diabetic Foot Care - Suardi Suardi; Dina Oktaviana; Fitriani Fitriani (Innovative Approaches in Health Science Journal, 2026)
Background: Type 2 Diabetes Mellitus (DM) is a chronic disease with a high risk of diabetic foot complications. During the COVID-19 pandemic, limited access to health services increased the importance of family-based self-care. This study aimed to analyze the relationship between family support and foot care adherence among patients with type 2 DM. Methods: A cross-sectional design was employed with 30 respondents selected through accidental sampling. Data were collected using a family support questionnaire and a foot care observation sheet. The Chi-square test was applied with a significance level of 0.05. Results: The results showed a significant relationship between family support and foot care adherence (p = 0.001). Conclusion: Strong family support improves patients' adherence in performing routine foot care.